2021
DOI: 10.3390/children8080696
|View full text |Cite
|
Sign up to set email alerts
|

How to Support Child Healthcare Nurses in Sweden to Promote Healthy Lifestyle Behaviors from the Start of Life

Abstract: Child healthcare (CHC) nurses have a key role in promoting and supporting healthy lifestyle behaviors from a young age. Thus, this study aims to investigate the perspectives of CHC nurses regarding discussing food introduction, physical activity/active play, and screen time with parents; explore facilitators and barriers influencing the discussion of healthy lifestyle behaviors with parents; and explore the perspectives of CHC nurses regarding a complementary program to promote healthy lifestyle behaviors from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Parents in this period are particularly concerned about their child's nutrition, and many parents experience worries related to diet or eating behaviours (Almqvist‐Tangen et al, 2017 ; Henström et al, 2020 ; Norlyk et al, 2019 ). Studies exploring PHNs' experiences have documented that counselling about food and feeding practices typically becomes challenging when the child reaches weaning age and begins to eat the same food as the rest of the family (Ersson et al, 2021 ; Holmberg Fagerlund et al, 2016 ). Our results further support the importance of reaching first‐time parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents in this period are particularly concerned about their child's nutrition, and many parents experience worries related to diet or eating behaviours (Almqvist‐Tangen et al, 2017 ; Henström et al, 2020 ; Norlyk et al, 2019 ). Studies exploring PHNs' experiences have documented that counselling about food and feeding practices typically becomes challenging when the child reaches weaning age and begins to eat the same food as the rest of the family (Ersson et al, 2021 ; Holmberg Fagerlund et al, 2016 ). Our results further support the importance of reaching first‐time parents.…”
Section: Discussionmentioning
confidence: 99%
“…A Norwegian study of nutrition counselling towards immigrant mothers found similar results (Holmberg Fagerlund et al, 2016 ). In a more recent Swedish study, the PHNs reported an increased need for support among today's parents on lifestyle issues, including nutrition‐related topics (Ersson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, approximately 25% of children have a migrant background [ 27 ] and at visits within CHC anyone that does not speak Swedish has the right to an interpreter. A study by Ersson et al [ 8 ] with Swedish CHC nurses has previously found that communication through an interpreter may affect how messages are delivered. As the Saga Stories in health talks intervention’s focus is the health dialogue between the nurse, parent(s), and child we have only included Swedish speaking participants to ensure the intervention is delivered as intended.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics will be used for the questionnaires and checklists. Semi-structured interviews with CHC nurses will be recorded (audio) and transcribed verbatim following the process described by Ersson et al [ 8 ]. Data will be analyzed using inductive thematic analysis [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation